2021
DOI: 10.1039/d0sc05625a
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated reactions of amines with carbon dioxide driven by superacid at the microdroplet interface

Abstract: Microdroplets display distinctive interfacial chemistry, manifested as accelerated reactions relative to those observed for the same reagents in bulk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 108 publications
(138 citation statements)
references
References 46 publications
5
130
1
2
Order By: Relevance
“…There was hardly any product formation at 0 h, without any time delay. Reactions in microdroplet are known to be accelerated, [28][29][30][31][32][33][34][35][36][37] however no such phenomenon was observed on the scale used here. HT-based DESI-MS analysis was also conducted to check the effect of different catalysts (Pd(acac) 2 , Pd(OAc) 2 , NiCl 2 , and CuCl 2 ) selecting the reaction between ethyl acrylate and Ezetimibe.…”
Section: Cà H Alkenylation Reaction On Ezetimibe (E) Using Ht-based Desi-ms Analysismentioning
confidence: 70%
“…There was hardly any product formation at 0 h, without any time delay. Reactions in microdroplet are known to be accelerated, [28][29][30][31][32][33][34][35][36][37] however no such phenomenon was observed on the scale used here. HT-based DESI-MS analysis was also conducted to check the effect of different catalysts (Pd(acac) 2 , Pd(OAc) 2 , NiCl 2 , and CuCl 2 ) selecting the reaction between ethyl acrylate and Ezetimibe.…”
Section: Cà H Alkenylation Reaction On Ezetimibe (E) Using Ht-based Desi-ms Analysismentioning
confidence: 70%
“…67 This acceleration phenomenon has been linked to the unique conditions at the droplet–air interface (reaction rates increase strongly with decreasing droplet size), and not simply to the increased concentration of reagents in evaporating droplets. 65,67,8688 Furthermore, it has been demonstrated that simply collecting the droplets sprayed from a reaction mixture allows the collection of milligram amounts of reaction product. 89 This capability confers a clear advantage for reaction screening: considerable product yields (obtained through a microdroplet-accelerated reaction) can be obtained with little to no incubation time prior to analysis.…”
Section: Resultsmentioning
confidence: 99%
“…We mixed the reactants at 50 µM, a condition shown to accelerate reactions to a great extent at both the air/solution 26,42,43 and solid/solution interfaces. 6,26,47,48 Figure 1 Comparison of reaction progress with glass microspheres (0.02 eq. silanolate groups, estimated) and without glass microspheres analysed by DESI-MS (average of 16 replicate analyses).…”
Section: Glass-promoted Chemical Reactions Studied By Nesi-msmentioning
confidence: 99%